The effectiveness of education and economic growth - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
It has been shown in the article that education in Poland is very efficient up to the middle level, though, this prepared human capital does not affect the economic growth in Poland measured by the GDP per capita. One of the main unsolved problems is the lack of cohesion of higher education and the national economy, which is expressed, among others, by the lack of the correlation between the graduate structure and the labor market. In the last twenty years the number of students in Poland has increased almost five times, hence the concern for a higher education quality improvement and, as a consequence, for economic growth. The article is an attempt of analysis of the reality of the above mentioned state.
Mathematical Economics, 2011, Nr 7 (14), s. 5-18
Keywords: effectiveness of education; economic growth